Portal hypertension imaging, diagnosis, and endovascular management - Saad, Wael E. A. (Thieme, 2018)
This authoritative volume is a comprehensive guide to the diagnosis and interventional management of portal hypertension. A potentially serious condition, portal hypertension presents considerable clinical challenges due to the delicate nature of the impacted organs, veins, and vessels. Several techniques have undergone significant advances since the second edition was published, including Transjugular Intrahepatic Portosystemic Shunt (TIPS), Balloon-Occluded Retrograde Transvenous Obliteration (BRTO), Balloon-Occluded Antegrade Transvenous Obliteration (BATO), and variations on TIPS, and all these are featured herein.